Piano starts here : the young Art Tatum - Parker, Robert Andrew (New York : Schwartz & Wade Books, 2008)
Explores early twentieth-century jazz pianist and virtuoso Art Tatum's passion and talent for playing the instrument, and includes illustrations and biographical information.
Includes bibliographical references.
Book Links (A.L.A.).
School Library Journal starred.
Wilson's Children.
Book Links (A.L.A.), January 2009.
Booklist starred, February 2008.
Keywords: Tatum, Art, -- 1910-1956 -- Childhood and youth -- Juvenile literature; Tatum, Art, -- 1910-1956.; Tatum, Art, -- 1910-1956.; Jazz musicians -- United States -- Biography -- Juvenile literature; African Americans -- Biography; Jazz musicians; African Americans -- Biography; Jazz musicians -- Biography